MicroRNA-mediated regulation of reactive astrocytes in central nervous system diseases - Fan, Yuansheng; Huang, Hui; Shao, Junfei; Huang, Weiyi (Frontiers in Molecular Neuroscience, 2023)
Astrocytes (AST) are abundant glial cells in the human brain, accounting for approximately 20%-50% percent of mammalian central nervous system (CNS) cells. They display essential functions necessary to sustain the physiological processes of the CNS, including maintaining neuronal structure, forming the blood-brain barrier, coordinating neuronal metabolism, maintaining the extracellular environment, regulating cerebral blood flow, stabilizing intercellular communication, participating in neurotransmitter synthesis, and defending against oxidative stress et al. During the pathological development of brain tumors, stroke, spinal cord injury (SCI), neurodegenerative diseases, and other neurological disorders, astrocytes undergo a series of highly heterogeneous changes, which are called reactive astrocytes, and mediate the corresponding pathophysiological process. However, the pathophysiological mechanisms of reactive astrocytes and their therapeutic relevance remain unclear. The microRNAs (miRNAs) are essential for cell differentiation, proliferation, and survival, which play a crucial role in the pathophysiological development of CNS diseases. In this review, we summarize the regulatory mechanism of miRNAs on reactive astrocytes in CNS diseases, which might provide a theoretical basis for the diagnosis and treatment of CNS diseases.